INOVASI LAYANAN PENDENGAR SIARAN RADIO DI ERA DIGITAL (STUDI KUALITATIF TENTANG EFEKTIVITAS KINERJA SIARAN DAN INTERAKSI PENDENGAR DI RADIO SWIBA KARANGANYAR) - Linda Pancaningrum; Ana Mayasari; Diana Sukorina; Erwinda Sam Anafih (Journal of Innovation Research and Knowledge, 2025)
Radio remains a mass communication medium that maintains an emotional connection with listeners, despite facing significant challenges in the digital era. This study aims to analyze service innovations implemented by Radio Swiba Karanganyar to improve broadcast performance, explore strategies for digital interaction with listeners, and identify driving and inhibiting factors in the implementation of digital radio services. The research method used a qualitative approach with a case study design. Data were collected through in-depth interviews with radio management, broadcasters, and active listeners, as well as participant observation and documentation. The results show that Radio Swiba Karanganyar develops service innovations through the use of online streaming, social media integration, and strengthening community-based content. Digital interaction has been shown to increase audience engagement, but faces obstacles such as limited human resources and technological adaptation. The study's conclusions confirm that the success of radio service innovation in the digital era depends not only on technology but also on strategies for building emotional connection with listeners